The role of neurocranial shape in defining the boundaries of an expanded Homo erectus hypodigm. Issue 92 (March 2016) - Baab, Karen L.
Abstract: The main goals of this study were to evaluate the distinctiveness of Homo erectus neurocranial shape relative to other closely related species, and assess the likelihood that particular fossils were correctly attributed to H. erectus given how shape variation related to geography, time and brain size. This was accomplished through analyses of several sets of landmarks designed to maximize the fossil sample, including 24 putative H. erectus fossils. The question of taxonomic differentiation was initially assessed for the type specimen (Trinil II) and morphologically similar Sangiran fossils and subsequently for increasingly inclusive definitions of H. erectus . Results indicated that H. erectus fossils from China, Indonesia, Georgia and East Africa shared a neurocranial shape that was distinct from that of other Plio-Pleistocene Homo taxa, a pattern only partially accounted for by brain size. Early Indonesian H. erectus formed a morphological "bridge" between earlier and later populations assigned to H. erectus from Africa and Asia, respectively. These results were combined with discrete characters to create a more complete species definition for H. erectus . There were two notable exceptions to the general pattern of H. erectus uniqueness. The 0.8–1.0 Ma (millions of years ago) Daka calvaria from Ethiopia consistently grouped with mid-Pleistocene Homo, including Bodo and Kabwe, rather than African or Asian H. erectus . In addition, Daka also exhibited several traits derived for mid-Pleistocene Homo, and its scaling pattern mirrored mid-Pleistocene Homo rather than H. erectus . Daka may have belonged to an "advanced" H. erectus population close to the root of Homo heidelbergensis sensu lato (s.l.), or to an early population of H. heidelbergensis s.l. . The 1.5 Ma KNM-ER 42700 specimen from Kenya exhibited a unique calvarial shape distinct from H. erectus despite the exclusion of problematic landmarks from the frontal bone. These unique aspects of shape were not present in two other subadult fossils, KNM-WT 15000 and D2700.